An institutional work view toward the internationalization of emerging market firms - Yan, Z.; Zhu, J.; Fan, David; Kalfadellis, P. (Pergamon, 2018)
© 2018 Elsevier Inc. Through the lens of institutional work – the institutionally embedded practice that aims to create, maintain, or disrupt the rules and shared meanings in social life, we discuss how an emerging economy's governments establish policies and regulations to develop outward foreign direct investment, and how domestic firms seek to shape these institutional arrangements to suit their interests and needs as they expand overseas. This study underscores the importance of the home country to multinational enterprises. We argue, the policymaking that underpins the internationalization of firms is not only a top-down (state inspired) but also a bottom-up process.